2017
DOI: 10.1002/prep.201700052
|View full text |Cite
|
Sign up to set email alerts
|

Explosion Performance of High‐Temperature Degraded Emulsion Explosives

Abstract: Experiments were conducted to study the underwater explosion performance of emulsion explosives (EE) after hot water bath. Spherical charges of EE with different sensitizers and hot water bath were prepared and tested. As for as-prepared charges, the detonation velocity experiments and underwater explosion experiments were carried out and the crystallization ratio was measured and calculated by the dissolution and neutralization method. The results showed an inverse relationship between explosion parameters (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Underwater explosion power is mainly composed of two parts, specific shock energy ( E s ) and specific bubble energy ( E b ), which could be characterized by the total energy ( E t ) [19]. They could be calculated as the following equations.…”
Section: Resultsmentioning
confidence: 99%
“…Underwater explosion power is mainly composed of two parts, specific shock energy ( E s ) and specific bubble energy ( E b ), which could be characterized by the total energy ( E t ) [19]. They could be calculated as the following equations.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, emulsion explosives have a strong work capacity and even surpass TNT in terms of brisance. However, the previous studies on underwater explosion experiments have revealed that the peak pressure, specific pulse, specific shock energy, and other parameters of emulsion explosives are relatively low, indicating that the energy output of emulsion explosives is currently weak and requires improvement [10].…”
Section: Introductionmentioning
confidence: 99%